2018
DOI: 10.1097/hcr.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Severity of Depression and Cardiac Risk Factors Among Women Referred to a Cardiac Rehabilitation and Prevention Clinic

Abstract: In this sample, we found a significant prevalence of untreated and undertreated depressive symptoms among women with, or at high risk of developing, cardiovascular disease. Additional strategies are needed to identify these patients early and link them to appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…75 Additionally, women may be un-or undertreated for depression: among 1075 women participating in primary prevention and cardiac rehabilitation, 39% still reported depressive symptoms meeting the threshold for depression. 76 Despite these well-recognized distinctions and gaps in care, few cohort studies or meta-analyses of psychological health and CVD risk have reported effects separately by sex. 41,42 This delineation is required to understand potential subgroup differences in psychological risk and to mount a better clinical offense for men and women, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…75 Additionally, women may be un-or undertreated for depression: among 1075 women participating in primary prevention and cardiac rehabilitation, 39% still reported depressive symptoms meeting the threshold for depression. 76 Despite these well-recognized distinctions and gaps in care, few cohort studies or meta-analyses of psychological health and CVD risk have reported effects separately by sex. 41,42 This delineation is required to understand potential subgroup differences in psychological risk and to mount a better clinical offense for men and women, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptom scores were compared across demographic and clinical variables. Older age, female gender, lower cardiorespiratory fitness (eg, peak metabolic equivalent of tasks [METs peak ] and peak oxygen uptake [V˙ o 2peak ])during an exercise task, higher body mass index (BMI, kg/m 2 ), lower education, surgical intervention, and attending fewer sessions of CR have been positively associated with depression severity and likelihood of cardiac events and were thus included 10,15,25–27…”
Section: Methodsmentioning
confidence: 99%
“…Older age, female gender, lower cardiorespiratory fitness (eg, peak metabolic equivalent of tasks [METs peak ] and peak oxygen uptake [V ˙ o 2peak ])during an exercise task, higher body mass index (BMI, kg/m 2 ), lower education, surgical intervention, and attending fewer sessions of CR have been positively associated with depression severity and likelihood of cardiac events and were thus included. 10,15,[25][26][27] Age, sex, and diagnosis were obtained through chart review of hospital records, educational attainment was self-reported through a single-item question, and current smoking was measured as ≥6 ppm expired carbon monoxide using a Smokerlyzer (CoVita). Both V ˙ o 2peak and METs peak were assessed through exercise tolerance tests (ETT).…”
Section: Benchmarking Variables and Demographicsmentioning
confidence: 99%
“…Podem ser localizados na literatura em diferenciadas populações/amostras (Bhardwaj et al, 2018), O que demonstra o valor do instrumento para a prática da pesquisa, já que pode apoiar aos pesquisadores na obtenção de dados sobre os sintomas depressivos (Lam, 2018).…”
Section: Instrumentosunclassified